Ejecucion de recursos de canon minero en la Universidad Nacional de Trujillo - Martell Aburto, Carmelo Gilberto (2013)
ABSTRACT The objective of this research was to examine the administrative management of the recruitment, programming and budget execution of fiscal years 2004 through 2008 and the incomes of the years 2009 to 2012 from the resources coming from mining operations in the “Region La Libertad” transferred to the “Universidad Nacional de Trujillo”, Peru. We proceeded to scrutinize each of the components of public investment projects scheduled for the years 2004, 2005, 2006, 2007 and 2008. We analyzed the approved budgets, schedules quarterly and monthly commitments as well as the source documents that support the phases of recruitment, engagement, earned money and payment. It showed a high efficiency and effectiveness in the administration of programming and implementation of current resources allowing the staff to feel pleased by a sense of achievement and full participation. However, the same treatment was not given to the administration and budget execution of other funding sources such as that from mining operations. From 2004 to 2008, resources from mining operations, the university received S/. 30'604,444.00, scheduled S/. 6'979,371.00 and executed only S/. 2'821,684.93, so it was not met the goals and objectives approved by the Institutional Strategic Plan and with the provisions of Law No.28411, General Law of the National Budget. From 2009 to 2012 mining resources it was transferred to the University an amount of S/. 69'866,775.00 out of which it was not executed, S/. 36’179,716.00 “Nuevos Soles”. We have been developed a proposal for improving the administrative and research activities at the university.